Sistem Pendukung Keputusan Dengan Menerapkan Metode TOPSIS Untuk Menentukan Siswa Terbaik - M.Yusuf Al-Hakim Syah; M.Rudi Sanjaya; Endang Lestari; Bayu Wijaya Putra (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
The process of selecting the best student in SMA N 4 OKU is currently based solely on the grades from the report book, which is not an optimal approach as there are many other aspects to consider. To address this issue, the TOPSIS method can be used to create a decision support system that considers criteria such as absence, individuality, extracurricular activities, accomplishments, and academic records. This method uses the principle that the selected alternative must be the farthesta froma thea negativea ideala solutiona anda closesta toa thea positivea ideal solution from a geometric perspective. Euclidean distance is used to calculate the optimal solution by measuring the proximity of each alternative. The result of this research is a website-based decision support system that helps teachers select the best students in SMA N 4 OKU by taking into account various criteria By using this method, the school can ensure that the best students are selected based on a comprehensive evaluation, which will ultimately contribute to the betterment of the school and its students.